1935
DOI: 10.1098/rspa.1935.0034
|View full text |Cite
|
Sign up to set email alerts
|

A study of the effect of curvature on fully developed turbulent flow

Abstract: 1—The solution of many important problems in aeronautics and hydraulics depends largely on the behaviour of turbulent flow along curved surfaces. In flow along plane surfaces the following method has proved to be successful. The laws of turbulent velocity distribution were investigated in straight tubes and channels of constant cross-section and the results applied to the boundary layer with variable thickness. The present work has undertaken with the idea of isolating the effect of curvature on the turbulent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1955
1955
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The measured velocity distribution 1102, 123,126,192,1931 showed that the maximum axial velocity was near the pipe outside wall with the slower moving fluid chiefly restricted to a relatively thin shedding layer near the walls. The flow pattern was more complex than in the laminar flow case [78] but has been qualitatively predicted using a two-equation turbulence model [57].…”
Section: (Iii) Turbulent Flowmentioning
confidence: 97%
“…The measured velocity distribution 1102, 123,126,192,1931 showed that the maximum axial velocity was near the pipe outside wall with the slower moving fluid chiefly restricted to a relatively thin shedding layer near the walls. The flow pattern was more complex than in the laminar flow case [78] but has been qualitatively predicted using a two-equation turbulence model [57].…”
Section: (Iii) Turbulent Flowmentioning
confidence: 97%
“…The computed et values are onegative in a small rane of radial distances. Both Wattendorf [10] and Eskinazi and Yeh [11] showed that in a fully-developed curved chaninel having ,an unsynmpetrical profile,, thẽ : location of the zero turbulent 'stress (-pu"v' did not occur at thepoint where "the velocity, derivative (au/ar) was zero, nor where the viscous shear was zero…”
mentioning
confidence: 99%